IMPLEMENTASI ALGORITMA FISHER-YATES SHUFFLE PADA APLIKASI QUIZ ONLINE MATERI PEMROGRAMAN DASAR - Bambang Pramono (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
Abstract The demand for IT professionals is increasing in line with digital transformation across various industries. Computer Science students are expected to possess programming competencies, particularly in terms of comprehending and implementing algorithms in programming languages. However, students often face challenges in mastering programming logic, which leads to a decline in their interest in the field. This study aims to develop an online quiz application designed to assist students in learning Basic Programming courses engagingly and interactively. The application employs the Fisher-Yates Shuffle method to randomize questions across six categories, comprising a total of 180 questions. The algorithm effectively shuffles and evenly distributes questions, ensuring that no student receives the same question sequence. This approach aimed to minimize the potential for cheating and enhance students' focus on learning. Results from the User Acceptance Testing (UAT) conducted using a questionnaire among 63 respondents indicated positive feedback, with 91% of the students providing favorable evaluations of the application's usability. The testing demonstrated that the application is beneficial and easy to use, fostering students' interest in and understanding of programming concepts. This application offers an intuitive interface and features that support interactive learning. In conclusion, utilizing the Fisher-Yates method within an online quiz application can effectively promote students' learning interest and enhance their comprehension of introductory computer science courses. Testing confirms that the application functions well and meets the user's requirements. Keywords: Online quiz application, Basic programming, Fisher-Yates Shuffle, User Acceptance Testing